1976
DOI: 10.1149/1.2132823
|View full text |Cite
|
Sign up to set email alerts
|

Tin (IV) Chloride Solution as a Sensitizer in Photoselective Metal Deposition

Abstract: Experiments were conducted which show that Sn(IV) bound to a substrate is capable, in conjunction with Pd(II), of catalyzing Ni-P plating and that this effect can be inhibited by u.v. light. Some of the parameters affecting the quality of the plating and u.v. inhibition were determined. It was also found that in order for u.v. irradiation to inhibit Ni-P plating, the radiation must be applied after the Pd(lI) activation step. In the case of copper, however, plating occurs only on the irradiated area of the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The sensitization and activation process by double immersion in SnClj and PdClj solutions has been studied [1][2][3] and one-step activation in PdClj-SnClj colloid solution followed by acceleration (HCl or NH4HF2 and others) was also investigated [4][5][6][7][8]. In contrast to the detailed chemical analyses presented in these researches [1][2][3][4][5][6][7][8], we studied the activation process through microstructure analysis by scanning transmission electron microscopy (STEM). This method provides information on sizes and distributions as well as chemical composition of the catalytic particles.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitization and activation process by double immersion in SnClj and PdClj solutions has been studied [1][2][3] and one-step activation in PdClj-SnClj colloid solution followed by acceleration (HCl or NH4HF2 and others) was also investigated [4][5][6][7][8]. In contrast to the detailed chemical analyses presented in these researches [1][2][3][4][5][6][7][8], we studied the activation process through microstructure analysis by scanning transmission electron microscopy (STEM). This method provides information on sizes and distributions as well as chemical composition of the catalytic particles.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of techniques that use electroless deposition for applying metal patterns onto polymeric substrates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Sharp (1), Chow et al (5), Schlesinger et al (6,7), and Baylis et al (8)(9)(10)(11) examined methods by which the electroless catalysts were photochemically activated (9) or deactivated (5). Their work led to examinations (12) of the effect of oxidized substrates on the activity of electroless catalysts.…”
mentioning
confidence: 99%
“…As noted earlier, we have shown that u.v. light can be utilized either as an inhibitor or as a stimulator for electroless plating (1). Thus, for instance, using a suitably aged Sn +4 sensitizing solution Cu plating will not be initiated unless the catalyst layer has been ex- posed to u.v.…”
Section: Discussionmentioning
confidence: 99%
“…Any discussion of this paper will appear in a Discussion Section to be published in the June 1980 JOURNAL. AI1 discussions for the June 1980 Discussion Section should be submitted by Feb. 1,1980.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation